Implementing product design assessment with sandwich-like architecture: A case study in an automotive company. (September 2020) - Gu, Jinheng; Liu, Changqing; Fu, Shenghui; Pang, Changle
Product design-oriented models are a decision-making problem with multiple criteria based on the assessment of product design factor that represent engineer judgments and customer desires, and are used to adapt to increasing competition and high levels of customization. Thus, in this work, a "sandwich-like" architecture and a hybrid integrated approach including triangle fuzzy numbers, quality function deployment, and the LeaderRank algorithm are respectively proposed to express and assess product designs more effectively. Additionally, the proposed approach is a measure study which can determine the design requirements, the relationships between product design and customer requirements, and the correlations among product values. The fuzzy analytical network process and LeaderRank algorithm are employed to evaluate the product design requirements and interaction between the product value and the uncertainty that exists in expert judgment. Besides, a case study is selected as an example to illustrate the "sandwich-like" architecture in the product design stage, and a priority analysis is performed to assess the importance degrees of product designs for customer needs, thereby providing optimization for product design and an effective approach to improve the product value.